(untitled) (Quaderni di Gargnano, 2021)
This paper is devoted to the protagonists of the Greek and Latin studies in Milan in the period of French domination, namely between the second and third decade of the sixteenth century. Despite the political and military instability of the time, Milan is still able to attract in its educational institutions important personalities (like Ricchieri, Negri, Telesio and Collinus) from the rest of Italy and also from Europe thanks to the direct interest in the culture of the king Francesco I and the patronage guaranteed to scholars by his treasurer in the city, Jean Grolier. In Milan these scholars made an important contribution to the progress of philological and humanistic studies with their teaching and publications. Il contributo è dedicato ai protagonisti degli studi greci e latini nella Milano della dominazione francese, in particolare tra il secondo e il terzo decennio del Cinquecento. Nonostante l’instabilità politico-militare del tempo, Milano è ancora in grado di attrarre nelle proprie istituzioni scolastiche importanti personalità (come Ricchieri, Negri, Telesio e Collinus) dal resto d’Italia e anche dall’Europa grazie al diretto interessamento in ambito culturale del sovrano Francesco I e al sostegno garantito agli eruditi dal suo tesoriere in città, Jean Grolier. Proprio a Milano questi eruditi hanno garantito con la loro docenza e le loro pubblicazioni un importante contributo al progresso degli studi filologici e umanistici.